Women in Morocco: Re-conceptualizing Religious Activism (American Journal of Islam and Society, 2013)
The recent political upheavals in the Arab world were marked bywomen’s significant presence in struggling for democracy alongsidemen. Muslim women activists in Morocco have particularly gainedlegitimacy in the context of the Arab Spring, which has brought theJustice and Development conservative political party to power. Thishas contributed to a shift from the elite liberal state feminism to amore legitimate religious activism. This introduces new spaces forcontention, taking into consideration that following the 2003Casablanca bombings, Morocco has taken a series of measures toabsorb the growing momentum of political Islam. One such measurehas been to restructure the religious field by means of reformingand controlling the dynamics of religion in Morocco; this was primarilymarked by the significant entry and deployment of womenin the religious field as religious leaders and scholars. These statetrainedfemale religious authorities offer spiritual counseling andreligious instruction to different social segments. Therefore, theyredefine parameters of religious authority and define a new modelof activism that seeks to cultivate collective pious conduct withinsociety and thus contribute to a comprehensive social reform.Therefore, this article explores the dynamics of female religiousauthority in Morocco in light of the current social and politicalchanges. I examine how these women construct authority as religiousleaders and how they endorse the state’s authority to controlthe dynamics of religion in Morocco and curb the voices of individualsor groups that operate outside of official Islam. I arguethat despite the fact that these female religious authorities areviewed as instruments of state propaganda, they are gaining widerlegitimacy and contributing greatly to the social welfare of theircommunities, which makes their “official” entry into the religiousdomain a serious step toward democracy and positive change.